STUDI LABORATORIUM PEMILIHAN ADDITIF PENSTABIL SHALE DI DALAM SISTEM LUMPUR KCL-POLIMER PADA TEMPERATUR TINGGI - Zakky Zakky; Bayu Satyawira; Samsol Samsol (President University, 2018)
Mud is one of the things that is very supportive in drilling operations, the design of the mud can affect the effectiveness of drilling work, the costs to be incurred, up to when the well is in production. Of course what is expected from a mud usage is low expenditure and drilling with optimal results. Drilling mud plays a very important role in a drilling operation. Drilling that can run quickly, safely and economically is greatly influenced by the conditions and sludge system used. The condition referred to here is how the properties or rheology of the mud. Whereas the mud system referred to here is a certain type of mud that must be used with regard to the state of the formation and borehole. Muddy KCl-POLYMER is a non-dispersed mud, where the hydration and dispersion process of the shale formation drilled must be maintained or maintained as much as possible. There are several ways to achieve this, the most common of which is to limit the amount of water that reacts with the shale, by covering the cutting produced by the shale with the polymer as soon as possible to prevent further reactions with water. In this study, we will analyze the use and physical properties of drilling mud using KCl-Polymer sludge which is carried out in the Trisakti University Laboratory of Petroleum Drilling and Production.